2022
DOI: 10.3389/fpsyt.2022.913640
|View full text |Cite
|
Sign up to set email alerts
|

The Status and Prescription Patterns of Opioid Utilization in a Large Comprehensive Teaching Hospital in China According to the Anatomical Therapeutic Chemical Classification/Defined Daily Dose Methodology

Abstract: BackgroundFew studies have analyzed opioid consumption and the average daily dose and duration for different patients in hospital settings in China. The aim of this study was to measure the status of and trends in prescribed opioids and the prescribing patterns at the Second Xiangya Hospital.MethodsThe data were obtained from the prescribed medicine database of the inpatient department. We included patients who were >18 years old and received any level of opioid analgesic between 2012 and 2017. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In addition, Shah et al found that the prevalence of opioid dependence among CP patients in the United States was 48.87%, and opioid dependence was associated with a higher incidence of anxiety and depression [28]. However, the use of opioids in China is quite conservative due to medical regulations [29]. Since patients cannot easily buy opioid analgesics, most of them tend to go to the hospital soon after the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Shah et al found that the prevalence of opioid dependence among CP patients in the United States was 48.87%, and opioid dependence was associated with a higher incidence of anxiety and depression [28]. However, the use of opioids in China is quite conservative due to medical regulations [29]. Since patients cannot easily buy opioid analgesics, most of them tend to go to the hospital soon after the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%